تصميم وحدات دراسية حاسوبية للتعبيرات الاصطلاحية في اللغة العربية : طلبة الجامعة الإسلامية العالمية بماليزيا نموذجا : دراسة لغوية حاسوبية - Amani binti Nawi (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2014)
The purpose of this study is to help Arabic learners to learn Arabic Idiomatic Expressions by designing a prototype courseware for them in learning these idioms and to investigate the difficulties experienced by the learners in identifying and understanding them. Previous studies have listed numerous reasons for the difficulties experienced by non-native Arabic learners in acquiring reading skills. One of the reasons is the inability to identify and understand the Idiomatic Expression in Arabic text which leads to their lack of understanding. This study was conducted by using systematic descriptive and analytical methodologies, where the descriptive approach was adopted to facilitate the gathering of information about Arabic Idioms and theories of learning through multimedia. In addition, there were three stages of scientific procedures in analytical approach. Firstly, learners' needs analysis which was completed before the phase of design. Secondly, experts' review analysis which was conducted during the design phase. The third stage was the analysis of formative evaluation by the learners after the completion of the development phase. The participants of this study were 70 students (30 students were selected during the needs analysis phase and 40 students were chosen during the evaluation phase) and 5 lecturers from the Department of Arabic Language and Literature of International Islamic University Malaysia. The prototype courseware implemented the theory of learning by Mayer and ADDIE model in its design and development. The results of this study show that students cannot identify Arabic idiomatic expressions and understand their meanings due to their lack of reading Arabic books, and that these idioms have not been taught in any particular subject or textbook, which results in their unawareness of the importance of these idioms and lack of practice in their usage. The result has also indicated that the contents included in this courseware are useful for the students who are specializing in Arabic language